Interaction between root hairs and soil phosphorus on rhizosphere priming of soil organic matter - Boilard, Gabriel; Bradley, Robert L.; Paterson, Eric; Sim, Allan; Brown, Lawrie K.; George, Timothy S.; Bainard, Luke; Carubba, Aaron (Soil biology & biochemistry, 2019)
We hypothesized that the rhizosphere priming effect (RPE) of soil organic matter by mutant barley lacking root hairs is dependant on a large network of symbiotic arbuscular mycorrhizal fungi (AMF). We thus predicted that fertilizing with phosphate-P would reduce AMF abundance and, in turn, reduce RPE of mutant barley. We packed microcosms with a P-responsive soil in which we grew mutant barley lacking root hairs as well as wild type barley and narrowleaf plantain, each possessing root hairs. One set of microcosms was fertilized with phosphate-P while another set was not fertilized. The plants were grown in a labelling chamber with 13C-depleted CO2. Soil respiration and δ13C of headspace CO2 were measured after 3, 4 and 5 weeks and RPE was calculated using an isotope mass balance approach. Root hair length was measured and soils were analyzed for the 16:1ω5 neutral lipid fatty acid (i.e. AMF biomarker). AMF abundance was greater, whereas RPE was lower, in mutant barley soil under low-P than under high-P conditions. In the other two plant-types, P had no effect on AMF or on RPE. As our results contradict our prediction, we propose an alternative explanation based on plant N demand under high-P. •Mutant plants lacking root hairs may depend on AMF to prime SOM decomposition.•Added P reduced AMF colonization and increased rhizosphere priming by mutant plants.•P had no such effects on wild-type plants with root hairs.•An increase of priming by mutant plants under high-P may be due to higher N demand.